Effect of Phosphate-based Glass Porous Microspheres (P30) Loaded with Extracellular Vesicle on Osteoblast Behaviour: In Vitro Study - Cahayadi, Sigit Daru; Nuzulia, Nur Aisyah; Boediono, Arief; Ahmed, Ifty; Nurhayati, Retno Wahyu; Sari, Yessie Widya; Juliandi, Berry (HAYATI Journal of Biosciences, 2025)
Bioactive materials, particularly phosphate-based glasses (PBG), hold great promise in bone repair due to their controllable degradation rates and bioactivity. This study evaluated PBG porous microspheres (P30) loaded with extracellular vesicles (EVs) for bone tissue engineering, focusing on osteogenesis, EV uptake, and cell invasion. P30 concentrations (5P30, 10P30, 50P30, 100P30, 500P30) were tested for their effects on calcification, EV uptake, and cell migration. Results showed that 100P30 exhibited optimal conditions for osteogenesis and EV delivery, with the highest calcification areas at both Day 7 and Day 14 and the most efficient EV internalization. Meanwhile, 500P30 demonstrated the highest cell migration, supporting pre-osteoblastic migration at this concentration. These findings indicate that 100P30 is ideal for mineralization and EV uptake, while 500P30 enhances cell invasion. This study highlights P30's versatility as a biomaterial for bone regeneration, with specific concentrations tailored to different regenerative goals. These results underscore the potential of P30 microspheres loaded with EVs as an effective strategy for promoting bone repair and regeneration.